2017
DOI: 10.1111/vru.12477
|View full text |Cite
|
Sign up to set email alerts
|

Incidental and Nonincidental Canine Thyroid Tumors Assessed by Multidetector Row Computed Tomography: A Single‐centre Cross Sectional Study in 4520 Dogs

Abstract: Thyroid nodules are common in dogs and are increasingly likely to be detected with the increased use of advanced imaging modalities. An unsuspected, nonpalpable, asymptomatic lesion, defined as a thyroid incidentaloma, may be discovered on an imaging study unrelated to the thyroid gland. The objective of this single-center cross-sectional study was to assess the prevalence and computed tomography (CT) characteristics of incidental and nonincidental thyroid tumors in a large population of dogs, using prospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 16 publications
0
23
0
Order By: Relevance
“…In the case of canine thyroid tumours, CT is recommended for both preoperative diagnosis and for staging [52,53]. It has also been recommended that any middle aged dog that has a body CT should be checked for incidental thyroid nodules as, although rare, they are identifiable [54]. CT is already regularly used for staging cancers, and each tumour type must be individually assessed as to which method is most appropriate for this vital process.…”
Section: Clinical and Research Investigations Into Soft Tissuesmentioning
confidence: 99%
“…In the case of canine thyroid tumours, CT is recommended for both preoperative diagnosis and for staging [52,53]. It has also been recommended that any middle aged dog that has a body CT should be checked for incidental thyroid nodules as, although rare, they are identifiable [54]. CT is already regularly used for staging cancers, and each tumour type must be individually assessed as to which method is most appropriate for this vital process.…”
Section: Clinical and Research Investigations Into Soft Tissuesmentioning
confidence: 99%
“…Thyroid tumours account for 1.1 to 3.8% of all neoplasms and approximately 10–15% of all head neoplasms in dogs [15]. In some studies, boxers, beagles, golden retrievers and Siberian huskies were more commonly affected compared to other breeds [2, 4–8].…”
Section: Introductionmentioning
confidence: 99%
“…In some studies, boxers, beagles, golden retrievers and Siberian huskies were more commonly affected compared to other breeds [2, 4–8]. However, another recent study found no association between breed and development of thyroid neoplasia [1]. Thyroid carcinomas are more frequently diagnosed antemortem than thyroid adenomas [1, 4–6, 15], which are often discovered serendipitously during physical examination or at necropsy [5, 8].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations